Quality control in nonstaple food markets: Evidence from India - Fafchamps, Marcel; Hill, Ruth Vargas; Minten, Bart (Wiley, 2008)
Using original survey data collected on growers, traders, processors, markets, and village communities, we will compare the situation in four states: Tamil Nadu, Uttar Pradesh, Maharashtra, and Orissa. We examine the way that information about crop attributes is conveyed (or not) along the value chain. We find that little information circulates about unobservable crop characteristics. Growers receive a price premium when they dry, grade, and pack their produce, but we find no evidence that information about crop salubrity or agricultural practices circulates through the value chain or that growers are encouraged to follow specific agricultural practices for quality purposes. Market infrastructure is deficient regarding sanitation, with few public toilets, inadequate drainage, and no coordinated pest control.